Transformative-Prophetic Leadership Pattern in Management of Education Institutions (Muhammad SAW Leadership Study) - Muhammad Tang; Abdul Rahim; Ismail Ismail (International Journal on Advanced Science, Education, and Religion, 2019)
This paper is here to describe and interpret the leadership pattern of Muhammad SAW. as a leadership model in managing transformative-prophetic educational institutions. Leadership in an organization or institution is one element that has a greater influence in achieving the goals of the institution. There has been a lot of research showing that the influence of leadership reaches 60-70% to achieve goals with organizations/institutions. Transformative-prophetic leadership pattern is a leadership pattern that moves to make an innovative change based on religious spiritual values. This study uses a qualitative method with a narrative study approach based on library research. The pattern or results of the research offered is that in educational institutions there are two elements that need to be developed, namely; human element and non human element by leaders who have a high character of rationality (Inspirational Motivation, Intellectual stimulation, Individualized Consideration, Idealized Influence) and integrated in themselves honest, integrity & responsible, computational & professional, communicative network building or networking. (The pattern image is in the sub discussion).